A step-by-step guide to SPSS for sport and exercise studies - Ntoumanis, Nikos (b, 2001)
SPSS is the international standard software package for data analysis in the social sciences. This book is the only SPSS guide designed specifically for students in the fields of sport, exercise and kinesiology. It Includes sport specific cases and data throughout.
Includes bibliographical references and index.
Keywords: Sports sciences -- Statistical methods -- Computer programs